2006
DOI: 10.3390/11080597
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Synthesis of 5-Arylidene-2-Imino-4-Thiazolidinones under Microwave Irradiation

Abstract: A rapid and easy solvent free one-pot synthesis of 5-arylidene-2-imino-4-thiazolidinones by condensation of the thioureas with chloroacetic acid and an aldehyde under microwave-irradiation is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 10 publications
1
39
0
Order By: Relevance
“…2527 A new transformation of multifunctional enoate esters 2 , occurring in 2-propanol solvent under mild (25 °C) conditions, produces various 5-alkylidene rhodanine derivatives typically favoring Z over E olefins by 30:1 to 7:1 ratios; routine silica gel column chromatography afforded the pure 5-( Z )-alkylidene rhodanines in the yields shown in Scheme 1. The (Z) -geometry of the 5-alkylidene rhodanines 3 – 5 is consistent with literature analogies 2831 and was confirmed by 1 H NMR spectroscopy. The 1 H NMR spectra of the crude reaction mixtures contained two distinct triplets for the single olefinic proton, the major triplet at 6.98–7.02 ppm and the minor triplet at 6.47–6.52 ppm.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…2527 A new transformation of multifunctional enoate esters 2 , occurring in 2-propanol solvent under mild (25 °C) conditions, produces various 5-alkylidene rhodanine derivatives typically favoring Z over E olefins by 30:1 to 7:1 ratios; routine silica gel column chromatography afforded the pure 5-( Z )-alkylidene rhodanines in the yields shown in Scheme 1. The (Z) -geometry of the 5-alkylidene rhodanines 3 – 5 is consistent with literature analogies 2831 and was confirmed by 1 H NMR spectroscopy. The 1 H NMR spectra of the crude reaction mixtures contained two distinct triplets for the single olefinic proton, the major triplet at 6.98–7.02 ppm and the minor triplet at 6.47–6.52 ppm.…”
supporting
confidence: 87%
“…These 1 H NMR data are consistent with the Z -isomer olefinic proton being further downfield then the E -isomer olefinic proton, because of deshielding from the carbonyl group. 2831 …”
mentioning
confidence: 99%
“…A common strategy involved in the prevailing synthetic protocols for 2-iminothiazolidin-4-ones [1214] is the cyclization of thioureas with α-halocarboxylic acids [15] or acyl halides [1617] or carboxylic esters [18]. These protocols are generally solution phase methods using organic solvents and acid scavengers.…”
Section: Introductionmentioning
confidence: 99%
“…Chemistry 5-Arylidene-2-imino-4-thiazolidinones 3a, 3c and 3d have been synthesized by the conventional heating of 2-imino-4-thiazolidinones 2 with the appropriate aldehyde under basic or acidic conditions [31,32]. Recently, compound 3a was prepared by a onepot three component solvent-free reaction of N,N-diphenylthiourea 1a with chloroacetic acid and benzaldehyde under microwave irradiation [33]. In this study, we synthesized compounds 3aed according to the latter reported procedure and their Z configuration was assigned as shown in Scheme 1 [34e38].…”
Section: Resultsmentioning
confidence: 99%